(untitled) (International journal of artificial intelligence, 2025)
The shift from traditional grammar-based methods to Communicative Language Teaching (CLT) has profoundly transformed the nature of language education and, more importantly, the role of the teacher within the classroom. This paper provides a theoretical analysis of the teacher’s role in the communicative classroom, emphasizing the transition from a teacher-centered to a learner-centered paradigm. Drawing upon the works of Hymes (1972), Canale and Swain (1980), Littlewood (1981), and Richards and Rodgers (2001), the study explores how teachers function as facilitators, guides, organizers, motivators, and evaluators in promoting communicative competence. It highlights that teachers are not merely transmitters of knowledge but active participants who create meaningful contexts for authentic interaction. The paper also discusses the challenges teachers encounter in implementing CLT and proposes strategies to enhance their effectiveness. Overall, the analysis demonstrates that the success of communicative classrooms depends largely on teachers’ ability to balance fluency and accuracy, autonomy and guidance, and control and flexibility.